S14.2 The CISNE Project: Implementation of POCT For Syphilis and HIV in Antenatal Care and Reproductive Health Services in Peru. (13th July 2013) - Garcia, P; Peeling, R; Mabey, D; Holmes, K; team, C
Abstract : Background: Congenital syphilis and syphilis in pregnancy in Peru persist as important public health issues, and improvement of screening/treatment for pregnant women remains challenging. Rapid syphilis testing (RST) allows simple and immediate diagnosis and treatment at a single clinic visit and could increase screening and treatment coverage reducing the incidence of stillbirth and congenital syphilis and generate in the long term a sustainable cost effective intervention. Methods: We tested the feasibility, performance, impact and cost-effectiveness of implementing RST in an underserved urban area at a biggest maternity hospital in Peru and a network of 16 peripheral health centres offering prenatal care in a periurban poor area in Callao-Ventanilla, Peru. RST (integrated with HIV rapid test: the "two for one") were offered at the first prenatal visit (ANC), at delivery and within miscarriage/abortion services. Results: Data from the baseline pre-implementation evaluation revealed limited coverage of screening and treatment services for maternal syphilis and a complex and inefficient system for ANC. RST was started in January 2010. Overall success of implementation was measured by rates of maternal syphilis screening and treatment coverage, partner treatment, and acceptability of RST among providers and patients. We also performed a cost-effectiveness analysis of RST against the Rapid Plasma Reagin (RPR). Attention was paid to the process of dissemination and transfer activities to the Ministry of Health of Peru, through the involvement of both the National Program of STIs and HIV and the Reproductive Health Program. National guidelines have been modified, and recommend the use of both tests, RST and rapid HIV testing in the screening of pregnant women. Conclusions: RST implementation was feasible, successful, acceptable and cost effective. Its introduction catalysed improvements in the quality of care, and by the end of the project it has been introduced in the country as a National policy.